An American lineage of Helicobacter pylori prophages found in Colombia - Muñoz, Angela B. (2022)
Background Helicobacter pylori is a human gastric carcinogen that is highly prevalent in Latin American. The prophages of H. pylori show a structured population and contribute to the diversity of this bacterium. However, H. pylori prophages present in American strains have not been described to date. In this study, we identified, characterized, and present the phylogenetic analysis of the prophages present in Colombian H. pylori strains. Methods To characterize Colombian H. pylori strains and their prophages, a Multilocus Sequences Typing (MLST) and a Prophage Sequences Typing (PST), using the integrase and holin genes, were performed. Furthermore, five Colombian H. pylori had their full genome sequenced, and six Colombian H.pylori retrieved from databases, allowing to determine the prophage complete genome and insertion site. Results The integrase gene frequency was 12.6% (27/213), while both integrase and holin genes were present in 4.2% (9/213) of the samples analyzed. The PST analysis showed that Colombian prophages belong to different populations, including hpSWEurope, hpNEurope, hpAfrica1, and a new population, named hpColombia. The MLST analysis classified most of the Colombia strains in the hpEurope population. Conclusions The new H. pylori prophage population revealed that Colombian prophages follow a unique evolutionary trajectory, contributing to bacterial diversity. The global H. pylori prophage phylogeny highlighted five phylogenetic groups, one more than previously reported. After the arrival of Europeans, the Colombian H. pylori bacteria and their prophages formed an independent evolutionary line to adapt to the new environment and new human hosts.